Discussion of "Constructability analysis in the design firm" by David Arditi, Ahmed Elhassan, and Y. Cengiz Toklu - Nima, Mekdam A.; Arditi, David A.; Elhassan, Ahmed; Toklu, Yusuf Cengiz (My University, 2004)
[Abstract Not Available]